PENGATURAN DOKTRIN SINGLE ECONOMIC ENTITY: STUDI PERBANDINGAN INDONESIA DAN UNI EROPA: Regulation of the Single Economic Entity Doctrine: A Comparative Study between Indonesia and the European Union - Wati, Widiya; Anggraini, Anna Maria Tri (AMICUS CURIAE, 2025)
Competition law has rapidly evolved alongside the dynamics of trade conducted by businesses. One notable development in Indonesia is the understanding of the Single Economic Entity (SEE) doctrine. This doctrine is often opposed by corporate law regimes that uphold the independence of companies. Therefore, it is crucial to examine how companies can be considered a single economic entity and how regulations differ between Indonesia and the European Union. This study employs a normative approach, using descriptive legal comparison with secondary data such as literature, regulations, and competition authority decisions from both regions. Data is analyzed qualitatively with deductive conclusions. The findings indicate that a group of companies is considered a single entity if its strategic policies are controlled by the holding company. There are both similarities and differences between Indonesia and the EU in their approach to this doctrine. The similarity is that both implicitly regulate SEE, while the difference lies in its application: in Indonesia, it was first applied in the Temasek Holding case in 2007, while the EU used it in the 1972 Deystuff case. To reduce misinterpretations, clearer explanations for business actors are necessary to prevent violations by business groups.